Cereal and nonfat milk support muscle recovery following exercise - Kammer, L.; Ding, Z.; Wang, B.; Hara, D.; Liao, Y.-H.; Ivy, J. L. (Journal of the International Society of Sports Nutrition, 2009)
This study compared the effects of ingesting cereal and nonfat milk (Cereal) and a carbohydrate-electrolyte sports drink (Drink) immediately following endurance exercise on muscle glycogen synthesis and the phosphorylation state of proteins controlling protein synthesis: Akt, mTOR, rpS6 and eIF4E.